The Mobile Learning Voyage - From Small Ripples to Massive Open Waters : 14th World Conference on Mobile and Contextual Learning, mLearn 2015, Venice, Italy, October 17-24, 2015, proceedings /: 14th World Conference on Mobile and Contextual Learning, mLearn 2015, Venice, Italy, October 17-24, 2015, proceedings. (2015) - Unknown
No abstract available